A protocol for a pilot randomised controlled trial of unguided internet cognitive behaviour therapy for grief in adolescents - Egan, Sarah; Munro, Caitlin; Pauley-Gadd, Sian B.; O'Brien, Amy; Callaghan, Thomas; Payne, Nicholas; Raghav, S.; Myers, Bronwyn; Hall, C.; Wilson, H.; Eisma, M.C.; Boelen, P.A.; et al. (2024)
Grief is highly prevalent in adolescents, however, there have been no studies investigating internet delivered cognitive behaviour therapy for grief in adolescents (ICBT-G-A). In this paper, the co-design of an unguided ICBT-G-A intervention is described, and a protocol outlined for a pilot randomised controlled trial of the intervention. Participants will be randomised to the intervention (delivered via eight modules over a four-week period) or a four-week waitlist control. Intervention participants will complete a follow-up assessment at one-month post-intervention (eight weeks from the pre-intervention assessment). The intervention outcomes assessed at pre-intervention, post-intervention and follow-up include wellbeing and symptoms of anxiety, depression, post-traumatic stress, and prolonged grief. User feedback on experiences and acceptability of the intervention will be sought and feasibility assessed via programmatic data on recruitment and attrition.